Empowering Housewives in Lampeout Village, Banda Aceh Through Training in Belwul Processing Skills (Starfruit Wuluh): Pemberdayaan Ibu-Ibu Rumah Tangga Desa Lampeout Banda Aceh Melalui Pelatihan Ketrampilan Pengolahan Belwul (Belimbing Wuluh) - Aryani, Irma; Rahmi, Rahmi; Syahrianursaifi, Syahrianursaifi; M. Syauqas Aziz; Nova Erliana (Universitas Lancang Kuning, 2024)
The Community Empowerment Activity (PKM) aims to enhance the skills of a group of housewives in the Lampeout Village, Banda Raya Subdistrict, Banda Aceh, through the processing of belimbing wuluh (starfruit) into innovative and marketable products. The processing includes turning belimbing wuluh into sweet belwul preserves, belwul syrup, ie limeng, and asam sunti. Additionally, this PKM focuses on harnessing the potential of previously less productive housewives, forming new entrepreneurial groups, and creating economically self-sufficient communities. The implementation method of this PKM activity includes counseling, training and hands-on practice, packaging and marketing, mentoring, and evaluation. This activity benefits the participants by increasing their knowledge and understanding of business management and the appropriate utilization of natural resources with market value. Based on the evaluation results, there has been an improvement in understanding and skills related to belimbing wuluh processing and the achievement of success indicators.